Indigenous beliefs and Zimbabwe’s War of Liberation: Inside the Metaphysics - Joshua Chakawa (MSU Press, 2023)
This article is a record of mysterious and miraculous events of the liberation war, as expressed by former combatants on either side of the conflict during the Zimbabwe’s liberation war in the 1970s. The research, therefore, widens understanding of African spirituality in times of war. Respondents were drawn from Mashonaland Central and West who were the Zimbabwe African National Liberation Army (ZANLA) and Zimbabwe People’s Revolutionary Army (ZIPRA) operatives in the respective areas. The special collaboration between guerrillas and spirit mediums in the early 1970s makes it imperative to find out if the taboos of the liberation struggle had any bearing to events which the fighters encountered during the war. Data was collected through studies of secondary sources and oral interviews. The major question, which the research answers is whether there was any relationship between metaphysics and battles which were fought during the war. In answering that question, the study examines African cosmology and reviews the development of relationships between liberation movements and spirit mediums. Lastly, it explores ways in which the metaphysical world manifested itself, how it regulated the behaviour of combatants/forces involved in the war and the living legacies of such beliefs to date. It is pivotal to note that the article contributes to issues of national healing, reconciliation and integration which the Zimbabwean government and other civil society organisations have been trying to spearhead, unsuccessfully though, since the attainment of independence in 1980. With a view of avoiding being cornered within controversial schools of thought, this research is not based on any theory, but on African worldviews in relation to religion.